Oil and Growth in the Republic of Congo - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 2006)
This paper investigates the linkages between oil and growth in Congo, where there appears to be no evidence of direct spillover effects. The empirical results suggest however that political instability has a negative effect on non-oil growth, and that the presence of oil could have fueled political instability by being associated with weakening institutions. The results also show that fiscal discipline is beneficial for growth. In addition, there are strong linkages between world oil prices and the real effective exchange rate, with movements in the latter having important indirect repercussions for growth.